University Industry Incubators: Igniting Global Startup Revolutions: Inkubator Industri Universitas: Memicu Revolusi Startup Global - Al-Sabaawe, Younis Mohammad; Hussein Albayati, Nashwan Hamdi; Saleh Al-Obaidy, Narmeen AbdulRazzaq (Universitas Muhammadiyah Sidoarjo, 2025)
Universities are pivotal engines of economic development, serving as the apex of the research hierarchy and the primary incubators of scientific knowledge that fuels entrepreneurial ventures. Despite this potential, the current collaboration between universities and the private sector falls short of expectations, leaving both parties under‑utilized. This study investigates how strategic cooperation between these actors can be strengthened and evaluates the feasibility of establishing research‑focused business incubators within universities to support private‑sector entrepreneurial projects. Guided by a novel philosophical framework that emphasizes systematic thinking and mutual social responsibility, the research adopts a mixed‑methods approach: a comprehensive literature review identifies best‑practice models; semi‑structured interviews with university administrators, faculty, and industry partners reveal prevailing obstacles and opportunities; and a Delphi panel refines a conceptual model for a university‑based research incubator. Findings indicate that the essential prerequisites—such as dedicated funding streams, interdisciplinary research clusters, technology‑transfer offices, and supportive policy environments—are already present in many institutions, yet they are often fragmented or under‑leveraged. Based on these insights, the proposed model recommends reallocating existing resources, synchronizing partnership timelines with regional development needs, and instituting formal mechanisms for joint project governance. Implementing such incubators promises to accelerate the translation of academic research into market‑ready innovations, boost private‑sector competitiveness, and generate broader societal benefits. The study thus offers a concrete roadmap for universities to become active catalysts of entrepreneurship, reinforcing their role as engines of sustainable economic growth.